2017
DOI: 10.1038/srep44906
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate Cryptochromes are Vestigial Flavoproteins

Abstract: All cryptochromes are currently classified as flavoproteins. In animals their best-described role is as components of the circadian clock. This circadian function is variable, and can be either light-dependent or -independent; the molecular origin of this difference is unknown. Type I animal cryptochromes are photoreceptors that entrain an organism’s clock to its environment, whereas Type II (including mammals) regulate circadian timing in a light-independent manner. Here, we reveal that, in contrast to Type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 57 publications
4
113
1
2
Order By: Relevance
“…We first investigated the temporal transcript expression of multifunctional Cry1 and Cry2. As expected, the Drosophila-like Cry1 (Gegear et al, 2010;Kutta et al, 2017), which is the posited magnetosensor, showed significantly up-regulated gene expression at 48h after molting into the 4th (+22.41%; F 1, 10 = 11.03, P = 0.008, partial η 2 = 0.52) and 5th (+27.12%; F 1, 10 = 14.34, P = 0.004, partial η 2 = 0.59) instar under the NZMF compared with the GMF. We also found significantly altered Cry2 expression pattern under the NZMF at 24h after molting into the 4th (+32.32%; F 1, 10 = 22.02, P = 0.001, partial η 2 = 0.69) and 5th instar (+65.43%; F 1, 10 = 34.93, P < 0.001, partial η 2 = 0.78), and at 48h after molting into the 5th instar (-16.65%; F 1, 10 = 10.34, P = 0.009, partial η 2 = 0.51; Figure 3a).…”
Section: Glucose Levels Of 5th Instar Nymphssupporting
confidence: 81%
See 1 more Smart Citation
“…We first investigated the temporal transcript expression of multifunctional Cry1 and Cry2. As expected, the Drosophila-like Cry1 (Gegear et al, 2010;Kutta et al, 2017), which is the posited magnetosensor, showed significantly up-regulated gene expression at 48h after molting into the 4th (+22.41%; F 1, 10 = 11.03, P = 0.008, partial η 2 = 0.52) and 5th (+27.12%; F 1, 10 = 14.34, P = 0.004, partial η 2 = 0.59) instar under the NZMF compared with the GMF. We also found significantly altered Cry2 expression pattern under the NZMF at 24h after molting into the 4th (+32.32%; F 1, 10 = 22.02, P = 0.001, partial η 2 = 0.69) and 5th instar (+65.43%; F 1, 10 = 34.93, P < 0.001, partial η 2 = 0.78), and at 48h after molting into the 5th instar (-16.65%; F 1, 10 = 10.34, P = 0.009, partial η 2 = 0.51; Figure 3a).…”
Section: Glucose Levels Of 5th Instar Nymphssupporting
confidence: 81%
“…Indeed, the vertebrate-like Cry2 gene has also been shown to be related to magnetoreception in cockroaches (Bazalova et al, 2016;Gegear et al, 2010). However, since it is classified as a vestigial flavoprotein (Kutta et al, 2017), and is unlikely to be the magnetoreceptor, Cry2 may work together with another chromophore (e.g., FAD in Drosophila-like Cry1) in magnetoreception. Moreover, given that Cry2 is a core component of the circadian clock (Jiang et al, 2018;Zhang et al, 2017), which has been shown to be sensitive to changes in magnetic field intensity (Fedele et al, 2014;Yoshii et al, 2009), the altered gene expression pattern of Cry2 observed in our study was more likely related to its role in circadian mechanisms.…”
Section: Glucose Levels Of 5th Instar Nymphsmentioning
confidence: 99%
“…However, since avian Cry1s do not appear to bind FAD [8], they are not able to function as photoreceptors and/or magnetoreceptors. The reason why they are located in the cytosol remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This C-terminal sequence varies by species and by the type of Cry, of which there are three in animals. The Type 2 animal Crys do not appear to possess FAD [8], and function as essential transcription factors and integral components of the transcription-translation feedback loop that constitutes the circadian clock in both vertebrates and invertebrates [912]. Type 1 Crys do possess FAD [13,14] and function to entrain the circadian clock to the light-dark cycle in some insects [1518].…”
Section: Introductionmentioning
confidence: 99%
“…Opsins are utilized as visual pigments in all Eumetazoa (Porter et al, 2012), while cryptochromes function as a photosensitive pigment in sponges (Muller et al, 2013;Rivera et al, 2012). In vertebrates, the role of cryptochromes as functional pigments has not been proven to date, but their role in circadian rhythmicity is highly probable (Kume et al, 1999;Kutta et al, 2017;Shearman et al, 2000). Although three cryptochrome genes have been identified in the B. floridae genome (Haug et al, 2015), their expression was not determined and their function remains elusive.…”
Section: Opsins As Key Molecular Determinants Of Light Detection In Amentioning
confidence: 99%